Effect of urea molasses minerals block on nutrient utilization, milk production and reproductive performance of crossbred cattle under semi arid ecosystem - KHADDA, B S; LATA, KANAK; KUMAR, RAJ; JADAV, J S; RAI, A K (The Indian Journal of Animal Sciences, 2014)
A trial was conducted to evaluate the effect of UMMB on overall performance of crossbred cattle and economics at KVK- Panchmahals under the semi- arid condition of Gujarat, India, during the year 2012–13. Lactating HF crossbred cows (20) were divided into groups T1 (control) and T2 (UMMB) of 10 cows in each. The feeding of selected animals in group (T1) was consisted of 5–6 kg dry fodder and 25 kg green fodder with 2.5 kg /day/animal concentrate mixture. In group T2, in addition to the above, a regular supply of UMMB as a lick was offered during the period of study without interruption. Supplementation of UMMB significantly improved the basal diet. UMMB supplemented cows produced 31.42% more milk with significantly higher milk yield in the animals of UMMB group as compared to control without any adverse affect on health of the animals. The postpartum oestrus period and service period reduced significantly in UMMB group than the control group. Reduction in cost of milk production/ litre was recorded 21.66% in crossbred cows supplemented with UMMB. Based on observations, it can be concluded that the feeding of UMMB improved the feed efficiency, milk production and composition and reproductive performance of crossbred cows under hot semi-arid ecosystem.